A novel methodology to assess land-based food self-reliance in the Southwest British Columbia bioregion. Issue 2 (15th February 2016) - Dorward, Caitlin; Smukler, Sean Michael; Mullinix, Kent
Abstract: There is a growing awareness that climate change, economic instability, resource limitations and population growth are impacting the capacity of the contemporary global food system to meet human nutrition needs. Although there is widespread recognition that food systems must evolve in the face of these issues, a polarized debate has emerged around the merit of global-versus-local approaches to this evolution. Local food system advocates argue that increasing food self-reliance will concomitantly benefit human health, the environment and local economies, while critics argue that only a globalized system will produce enough calories to efficiently and economically feed the world. This debate is strong in British Columbia (BC), Canada, where residents and food security experts have called for increased food self-reliance while the provincial government largely supports export-oriented agriculture. As elsewhere, however, in BC this debate takes place in absence of an understanding of capacity for food self-reliance. The few studies that have previously evaluated self-reliance in this region have been limited in their approach in a number of ways. In this study we use a novel methodology to assess current (2011) status of land-based food self-reliance for a diet satisfying nutritional recommendations and food preferences that accounts for seasonality of crop production and the source of livestock feed, and applied it to the Southwest BC bioregion (SWBC) as a case study. We found that agricultural land use in SWBC is dominated by hay, pasture and corn silage, followed by fruits and vegetables. Fruit and vegetable production comprise 87% of total food crop production in SWBC by weight, and a substantial amount is produced in quantities beyond SWBC need per crop type, representing an export focused commodity with limited contribution to food self-reliance. Results illustrate that SWBC is a major producer of livestock products, but these industries rely on feed grain imports. The production of feed grain could therefore be considered a major constraint on self-reliance; SWBC's total dietary self-reliance is 12% if discounting livestock feed imports or 40% if including them. Results demonstrate that a diet including foods that cannot be grown in the region or consumed fresh out of season, limits potential food self-reliance. Our methods reveal the value of factoring dietary recommendations and food consumption patterns into food self-reliance assessments and the necessity of accounting for the source of livestock feed to fully understand the self-reliance status of a region.